NILAI EKONOMI PEMANFAATAN FLORA DI TAMAN NASIONAL BALURAN - Joko Mulyo Ichtiarso (Wanamukti: Jurnal Penelitian Kehutanan, 2020)
One of ecosystem services that is used by buffer community village flora thatis component ecosystem at Baluran National Park (BNP). Form of flora htat isusedy by community are fruit, understrorey, tubers, and so on. This motivates tocalculate economic value of flora as component ecosystem. The object of research is to know how much economic value of ecosystem services especially from fauna in BNP which has been utized by community buffer village and dependence on BNP. The method of research by quantitative and qualitative approaches. Data collected are typological conditions of BNP community buffer village, human resources who used the services of BNP ecosystem services, identity of community who used ecosystem services, types of ecosystem services used by community, harvest season, location of ecosystem services, community income that uses ecosystem and dependence on BNP ecosystem services. The result of research are economic value of flora that is component of ecosystem that have been utilized by community buffer village are candlenut (Rp. 1,306,694,400), tamarind (Rp. 1,292,085,000), acacia (Rp. 3,951,415,200), gadung (Rp. 924,160,800), firewood (Rp. 1,409,100,000), grass (Rp. 5,154,600,000), and ramban (Rp. 72,240,000). Total economic is Rp.14,110,295,400,- per year.Keywords: Flora, Ecosystem services, Baluran National Park